Control-oriented modeling and analysis of direct energy balance in coal-fired boiler-turbine unit. (October 2016) - Sun, Li; Li, Donghai; Lee, Kwang Y.; Xue, Yali
Abstract: Direct energy balance (DEB) coordinated control scheme is widely used by field engineers in coal-fired power plants while attracting little attention in the academic community. This paper aims to derive a mathematical model that is suitable for DEB research. To balance the model's fidelity and simplicity, the power plant is divided into three transformation modules and, using conservation laws, a dynamic model is developed to describe each module. Within reasonable assumptions, numerous module equations are combined to yield a 6th-order nonlinear model. Time constants of the model are identified based on Pareto optimization. Model accuracy is confirmed using field measurements from a 300 MW coal-fired power plant. Based on the linearized model, the merits of the DEB control structure are analyzed. It is confirmed that the DEB control is sufficient to fulfill the fundamental goals of power plant regulation. An illustration of performance improvement is given by introducing gain scheduling techniques to the DEB structure. The proposed model can provide groundwork for future development of advanced control algorithms under the DEB structure. Highlights: A mathematical model of boiler-turbine unit is derived and validated. The whole plant is separated as three transformation modules for simplicity. The inherent properties of DEB are analyzed based on the proposed model. The model provides groundwork for future advanced control design.